1984
DOI: 10.1093/oxfordjournals.aje.a113870
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Nutrition in Adults the National Health and Nutrition Examination Survey1

Abstract: To provide a contemporary profile of blood pressure and nutritional and sociodemographic relationships in the adult US population, data from the first National Health and Nutrition Examination Survey ( NHANES -I), 1971-1975, were analyzed. Systolic and diastolic blood pressures increased with increasing age, but trends were different by sex and race groups. Body mass index (weight/ height2 ) was the nutritional factor most strongly and consistently related to blood pressure. Among dietary constituents, alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(48 citation statements)
references
References 0 publications
5
42
0
1
Order By: Relevance
“…Similar types of findings were reported by different researchers of different countries [2][3][4][5][6][7][8]13 . On the contrary, similar observations were made by other researchers but they did not find any significant difference in body mass index value between the groups.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar types of findings were reported by different researchers of different countries [2][3][4][5][6][7][8]13 . On the contrary, similar observations were made by other researchers but they did not find any significant difference in body mass index value between the groups.…”
Section: Discussionsupporting
confidence: 89%
“…Overweight and obesity are the fifth leading risk for global deaths, with at least 2.8 million adult dying annually as a result of Bangladesh J Medicine 2017; 28 : 28-33 obesity 7 .Obesity has been associated with chronic non-communicable diseases like hypertension, coronary heart disease, type 2 diabetes, dyslipidemia, chronic kidney disease, cancer and arthritis. 8 A number of studies have shown the risk of obesity increases the hypertension .In the Framingham study, a 10% rise in body weight is associated with a 7mmhg rise systolic blood pressure 9 The National Health and Nutrition Examination survey reported linear association between increase in body mass index and systolic, diastolic and pulse pressure in the American population. It is reported that an increase of body mass index of a 1.75 kg/m2 in men and 1.25kg/m2 in women will cause 1 mm Hg rise in systolic blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Bodily weight and BP correlate positively over the normal and the arbitrarily defined abnormal ranges of these variables (Figure 1). 21 A high intake of sodium, which is a risk factor for the development of hypertension, was identified as a strong independent risk factor for coronary heart disease among obese individuals in the NHANES I. 22 The association between obesity and hypertension, which is independent of ethnicity and socio- Figure 1 Relationship between mean blood pressure (BP), body mass index and age from a population survey carried out in Uruguay.…”
Section: Body Weight and Hypertensionmentioning
confidence: 99%
“…A published descriptive report details these efforts and the study content. 9 The papers in the Journal supplement examine issues related to health care utilization, health risk behaviors, perinatal health, and dental health. ' Other published results of HHANES have supported some of the previous research in areas such as the prevalence of diabetes and gallstones.…”
Section: At Last-a View Of Hispanic Health and Nutritional Statusmentioning
confidence: 99%